1980
DOI: 10.1002/mana.19800990103
|View full text |Cite
|
Sign up to set email alerts
|

Generating Systems of Sets and Quotients of Surjeetive Operator Ideals

Abstract: The paper gives i t characterization of right-hand quotients d = Al o -4;' of surjective operat,or ideals A, iiiid 112 which refers to so cnlled "generitting systems of sets". Siinultmeously the corresponding "inversion formulas" Basic concepts and notationsThe present paper deals with a special method for geneiating o p n t o r ideals o ?~ the class of all UANACH spaces. The general riotion of an operator ideal can he looked np in [lo] and in various research papers.The teriii "operator" refer? to a eontinuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 8 publications
0
29
0
2
Order By: Relevance
“…Motivated by this work, Ryan [23] carried out a similar study of weakly compact holomorphic mappings, obtaining similar result to those in [6]. In 2000, González and Gutiérrez [17], using the theory of generating system of sets of Stephani [25], extend some of the results of [6] and [23] to a wide class of holomorphic mappings.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Motivated by this work, Ryan [23] carried out a similar study of weakly compact holomorphic mappings, obtaining similar result to those in [6]. In 2000, González and Gutiérrez [17], using the theory of generating system of sets of Stephani [25], extend some of the results of [6] and [23] to a wide class of holomorphic mappings.…”
Section: Introductionmentioning
confidence: 68%
“…Also, we say that A is surjective if A = A sur isometrically. For a Banach operator ideal A, a set M ⊂ X is A-bounded if there exist a Banach space Z and a linear operator T ∈ A(Z; Y ) such that M ⊂ T (B Z ), see [25]. In the case of A = W, the W-bounded sets coincide with the weakly compact sets and if A = K, we obtain the compact sets.…”
Section: Preliminariesmentioning
confidence: 99%
“…Proposition 2.4 can be used to provide many further useful examples of ideal topologies. Given an operator ideal I and a Banach space E, according to [63,28,37] we define…”
Section: Ideal Topologiesmentioning
confidence: 99%
“…(We will not be any more precise than this here, simply referring the reader to [4] w167 4.7.) We will show that ideals in a yon Neumann algebra satisfy properties analogous to certain charaeterisations of injective and surjective operator ideals studied by Stephani ([6], [7] and [8]). As a consequence we show that some of the known properties of injective and surjective operator ideals have analogues in the setting of ideals in yon Neumann algebras.…”
mentioning
confidence: 90%
“…Dual to the notion of 'generating topology' is Stephani's 'generating systems of sets'. In [7] it is shown that if an operator ideal is surjective then it can be characterised in terms of these generating systems of sets. This result can be compared to the bornological characterisation mentioned above.…”
mentioning
confidence: 99%